Predicting Habitat Suitability for the Endangered Green Peafowl (Pavo muticus L., 1766) in Thailand’s Western Stronghold under Future Climate Scenarios: 10.32526/ennrj/23/20250081 - Prommakul , Kornkanok; Noowong , Jedsada; Charaspet , Khwanrutai; Kaewdee , Bunyatiporn; Siripattaranukul , Kittiwara; Duengkae , Prateep; Simchareon , Saksit; Sukmasuang, Ronglarp (Environment and Natural Resources Journal, 2025)
The green peafowl (Pavo muticus L., 1766) is endangered globally. This study evaluates environmental factors shaping its habitat in key Thai strongholds to identify current habitat suitability and predict future changes under climate scenarios. Current and projected climate data from 2020 to 2100 were analyzed under four scenarios of 20 years each: at present, in the near future, mid future and far future, using species distribution modelling with MaxEnt and SSP2-4.5 to assess potential impacts. The results show that the key green peafowl habitat factors included elevation, slope, streams, isothermality and annual precipitation. Mixed deciduous forests were the most critical forest types for the species. Moderately and highly suitable habitats for the green peafowl covered approximately 5% of the sanctuary. However, well suitable habitat is projected to decrease markedly, representing a 21.25% decline. Strict management of these crucial areas is essential. Moreover, expanding protected areas, networks, and conservation strategies are vital for addressing challenges arising from rapid global environmental change.